2021
DOI: 10.1177/23259671211012364
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Tommy John Surgery: The Identification of Trends in Pitch Selection, Velocity, and Spin Rate Before Ulnar Collateral Ligament Reconstruction in Major League Baseball Pitchers

Abstract: Background: Ulnar collateral ligament (UCL) reconstruction is a common surgery among Major League Baseball (MLB) pitchers that results in a significant number of missed games. Little has been reported regarding game-by-game trends that can identify those on the verge of becoming injured. Purpose: To determine if there is a patterned change in MLB pitchers’ pitch selection, velocity, or spin rate in games leading up to Tommy John surgery that may predict subsequent UCL surgery. Study Design: Case series; Level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 29 publications
(43 reference statements)
0
20
0
Order By: Relevance
“…The authors looked at the previous 15 games before UCL injury and reported a statistically significant decrease in 4FB, 2FB, and SL velocity, as well as a significant decrease in 4FB spin rate leading up to injury. 20 The study hypothesized that the drop in velocity and spin rate may be related to muscle fatigue or altered pitching mechanics before impending injury. 20 In the present study, there were no significant differences in 4FB or SL velocity after RTP after UCLR, although a significant decrease was seen for 2FB in the first year after return (which returned to a nonsignificant difference in the second year).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors looked at the previous 15 games before UCL injury and reported a statistically significant decrease in 4FB, 2FB, and SL velocity, as well as a significant decrease in 4FB spin rate leading up to injury. 20 The study hypothesized that the drop in velocity and spin rate may be related to muscle fatigue or altered pitching mechanics before impending injury. 20 In the present study, there were no significant differences in 4FB or SL velocity after RTP after UCLR, although a significant decrease was seen for 2FB in the first year after return (which returned to a nonsignificant difference in the second year).…”
Section: Discussionmentioning
confidence: 99%
“…20 The study hypothesized that the drop in velocity and spin rate may be related to muscle fatigue or altered pitching mechanics before impending injury. 20 In the present study, there were no significant differences in 4FB or SL velocity after RTP after UCLR, although a significant decrease was seen for 2FB in the first year after return (which returned to a nonsignificant difference in the second year). Of note, that difference was less than a mile per hour, so from a performance standpoint it is difficult to determine if this would have an effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations